AN ANALYSIS OF STUDENTS' PERCEPTION OF CREATIVE WRITING THROUGH THE INSTAGRAM PLATFORM - Wati, May Syahra; Dauyah, Ema; Elyza, Ferlya (Jurnal Dedikasi Pendidikan, 2025)
This study portrays students' perceptions of using Instagram as a medium for creative writing. Furthermore, this study also aims to explore in-depth interactions that occur on Instagram as a medium for creative writing. The research method applied was a mixed-methods approach, combining quantitative and qualitative research methods. Data was collected through the distribution of questionnaires and interviews. The questionnaire issued 15 closed-ended questions, while the interviews comprised 5 semi-structured interviews. The sample for this research consisted of a mix of sixth-semester and fourth-semester students, including 10 students from the sixth semester and 5 students from the fourth semester, totaling 15 samples from the English Education program for the Academic Year 2024. Based on the data analysis of the questionnaire, it was revealed that students had a very positive perception and good attitude toward using Instagram as a medium for creative writing. Additionally, the interview data showed that the interactions occurring on Instagram had beneficial effects and were perceived positively by the students. Particularly, it was depicted that creative writing on Instagram enhances students' motivation, enthusiasm, and self-confidence in writing creatively. It, additionally, helps them expand their ideas into coherent pieces of writing. By engaging in creative writing on Instagram, students could observe the development of their writing skills over time. Therefore, this study's results indicated using Instagram as a medium for creative writing. It is an effective way to enhance writing skills and foster students’ motivation and self-confidence.